Analisis Technology Acceptance Model (TAM) Terhadap Penggunaan Aplikasi Gojek Pada Mahasiswa Di Kota Palembang - Mardhiyah, Nyayu Sakinatul; Rusydi, M; Azwari, Peni Cahaya (Faculty of Economic and Business, 2020)
This research aims to find out how technology in the form of gojek can be well received by colleges in Palembang. The framework has been developed based on the TAM and TRA with quantitative research methods in the form of SEM Amos 21. The results of the research are usefulness and ease of use have a positive and significant effect on behavioral intention of use, usefulness, ease of use and behavioral intention of use have a positive and significant effect on actual system use, the last usefulness and ease of use have a positive and significant effect on actual system use through behavioral intention of use. Based on these results it can be concluded that the subject has been well received by Palembang colleges through TAM and TRA as the grand theory.